Saberes docentes pressupostos em um livro didático e em um manual do professor de língua espanhola: implicações na formação docente - Silva, Silvana Aparecida Duarte da (2017)
The present study had the objective of identifying and problematizing the teaching knowledge assumed in some pre-selected sections from the Spanish-language book: Enlaces: Español para Jóvenes Brasileños volume1 (OSMAN, 2013), approved by the Programa Nacional do Livro Didático (PNLD, 2015) and also, observing the guidelines proposed by the Teacher's Guide (TG) in the same work in order to identify and problematize the teaching knowledge as well. As a theoretical basis, a brief reflection was made on the importance of the textbook and the teacher's guide for foreign language teaching, and the evolution and main characteristics of the PNLD were presented. The theoretical basis was based on Tardif (2002, 2005, and 2012) and Gauthier et al (2013). Nevertheless, to carry out the analysis of the textbook, it was only used the studies of Gauthier et al (2013), since it presents more indications of the types of knowledge that are mobilized by the teachers, besides being based on a vision of a pedagogical practice more pragmatic. Then the analysis was based on a descriptive and interpretative view of the teacher knowledge assumed in the analyzed pages and on the knowledge observed through what the teacher's guide prescribes. As a result, the analyses showed the predominance of the "knowledge of pedagogical action" in the guidelines contained in the teacher's guide. It also demonstrated that the recommendations are not sufficient for the concreteness of the specific objectives of the activities neither for the attitudinal proposals listed by the sections of the units defined for analysis, requesting other knowledge for the adequacy of the proposed contents too. In this sense, the recurrence of the knowledge of pedagogical action has indicated that for the good performance of a teaching based on a textbook will depend mainly, on the acuity of the teacher, for having to adapt the book in the attempt to accomplish the disciplinary content and mainly to achieve the attitudinal contents and objectives stipulated by the sections.